2013
DOI: 10.1186/1756-0500-6-455
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose aspirin-associated upper gastric and duodenal ulcers in Japanese patients with no previous history of peptic ulcers

Abstract: BackgroundLong-term administration of low-dose aspirin (LDA) is associated with a greater risk of adverse events, including gastroduodenal ulcers. The purpose of this study was to identify the risk factors for and assess the role of medication use in the development of peptic ulcer disease in Japanese patients with no history of peptic ulcers.MethodsConsecutive outpatients receiving LDA (75 mg/day) who underwent esophagogastroduodenoscopy between January and December 2010 were enrolled. Clinical parameters, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
0
11
2
2
Order By: Relevance
“…Overall, 100 µg/mL aspirin corresponds to a value of between 0.5 and 1 mM aspirin, which is within the therapeutic dose range of the drug (0.1-2 mM) (26). In addition, according to pharmacology experiments, 100 μg/mL aspirin is considered as a low level, and approximately 90%, which is good a percentage, of plasma salicylate is bound to albumin (27). Overall, 1 mM betaine is used for the methyl donor substrate supplementation (28).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, 100 µg/mL aspirin corresponds to a value of between 0.5 and 1 mM aspirin, which is within the therapeutic dose range of the drug (0.1-2 mM) (26). In addition, according to pharmacology experiments, 100 μg/mL aspirin is considered as a low level, and approximately 90%, which is good a percentage, of plasma salicylate is bound to albumin (27). Overall, 1 mM betaine is used for the methyl donor substrate supplementation (28).…”
Section: Methodsmentioning
confidence: 99%
“…La producción de moco y bicarbonato, los fosfolípidos de membrana, el rápido recambio celular, la angiogénesis y la delicada red microvascular representan las principales barreras de defensa frente a los factores agresores; entre estos últimos sobresalen la infección por Helicobacter pylori y el consumo crónico de antiinflamatorios no esteroideos (AINE) (1,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionunclassified
“…We selected 19 highquality studies, which consisted of 46,674 patients with diabetes and 159,630 patients without diabetes. Kawamura et al reported that DM was more frequent in patients with peptic ulcers than in those without peptic ulcers (32). Seven investigations, which included 44,647 DM patients and 141,119 non-diabetic patients, concentrated on the relationship between the morbidity rate in PUB and DM.…”
Section: Study Selectionmentioning
confidence: 99%